تاثير اضافة الاكاسيد المعدنية والمعالجة الحرارية بتقنية الليزر على بعض مواد الترميم في طب الاسنان - محمد حليمة جابر; صالح فارس ابراهيم; حمدي نجدت; اسماعيل حقي (Al-Nahrain Journal of Science, 2010)
This work was aimed to study the effect ofmetal oxides addition and thermal treatmentusing laser technic on the mechanicalproperties of zinc polycarboxylate and zincphosphate cements. hardness, compressivestrength and tensil strength were measured forthree different prepaired specimens , ist fromcommercially available cements, 2nd afteraddition of magnesium and aluminum oxidesand 3rd after thermal treatment using lasertechnic .the results exhibit a valuableincrement in the compressive strength wherelow increments were observed for othermechanical properties. Therefore thepolycarboxylate cement with the newmodification have god mechanicalspecification compared to zinc phosphatecement and high adhesive force appropriate tometal and enamel.